Conflict of law rules and international trade : a transaction costs approach - Roland Kirstein; Dieter Schmidtchen; Alexander R. Neunzig (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2004)
Drawing on Transaction Costs Economics, this paper develops a new approach to conflict of law rules. It outlines a concept of constitutional uncertainty in international trade and presents a model of international transactions in the presence of a diversity of legal orders. We develop a general analytical concept of an international legal order and analyze the impact of different specifications of international legal orders on international transactions. – – Der Beitrag stellt eine auf der Transaktionskosten-Ökonomik basierende Analyse von Kollisionsnormen vor. Hierzu wird zunächst das Konzept der konstitionellen Unsicherheit im internationalen Handel eingeführt. Dann werden internationale Transaktionen im Schatten verschiedener Rechtsordnungen spieltheoretisch modelliert. Das Modell ermöglicht die Analyse internationaler Rechtsordnungen und ihrer Auswirkungen auf die Effizienz internationaler Handelsbeziehungen.
Keywords: F15; F02; K33; 330; conflict of law; international private law; transaction costs; enforcement of judgments.; Internationales Privatrecht; Rechtsdurchsetzung; Transaktionskosten; Aussenwirtschaft; Internationale Wirtschaftsbeziehungen; Gerichtliche Prozesskosten; Spieltheorie; Theorie; Welt